Analisis Pendapatan Nilai Tambah Dan Pemasaran Olahan Tanaman Rimpang Jahe Pada KWT Sekar Mewangi - Clariza Sherllyana; Zulkarnain Zulkarnain; Djoko Umar Said; Kaizan Kaizan (Pusat Penelitian dan Pengabdian pada Masyarakat Sekolah Tinggi Ilmu Pertanian Dharma Wacana, 2023)
Ginger is a type of medicinal plant that has several types of varieties including red ginger. Red ginger plants have the potential to be processed into processed products that have added value. This study aims to (1) to be able to find out the income from instant red ginger agro-industry in KWT Sekar Mewangi. (2) to be able to find out the added value of red ginger into instant ginger on fragrant KWT Sekar Mewangi. (3) to be able to find out the marketing channel for instant ginger in KWT Sekar Mewangi Untoro Village Trimurjo District Central Lampung Regency. The determination of the research area used the purposive method, with the population being 30 members of the mewangi bulkhead KWT and the sample being the Sekar Mewangi head of the KWT. The analytical method used in this research is value added and descriptive analysis. Data colletion method used in this research are primary data and secondary data. Data analysis used added value analysis and marketing channels. It was concluded that the red ginger business carried out by KWT Sekar Mewangi was profitable because it could produce added value products and increase farmers’ income. Therefore, this effort needs to be developed in a better direction.